2016
DOI: 10.1080/00016489.2016.1255775
|View full text |Cite
|
Sign up to set email alerts
|

Meniere’s, migraine, and motion sickness

Abstract: METHODSWe conducted an online survey that posed diagnostic and disease questions before addressing frequency of headaches, migraines, visual display dizziness (VDD), syncope, social life and work impact of dizziness (SWID4) and motion sickness susceptibility (MSSQ). The two groups were: diagnosed MD individuals with hearing loss (n=751) and non-MD individuals in the control group (n=400). RESULTSThe MD group showed significantly elevated MSS, more headache and migraine, increased VDD, higher SWID4 scores, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
5
20
0
1
Order By: Relevance
“…In our cohort, we found that 69% of patients referred at least one of the pediatric precursors of migraine; in particular, 42.8% of subjects referred motion sickness. Recent studies have emphasized how motion sickness is a common finding in the general population and it has a strong genetic contribution . Our data are in line with a previously published work reporting a rate of migraine equivalents of 70.3% and motion sickness of 40.5% in a sample of over 1000 pediatric patients mostly with migrainous headaches .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our cohort, we found that 69% of patients referred at least one of the pediatric precursors of migraine; in particular, 42.8% of subjects referred motion sickness. Recent studies have emphasized how motion sickness is a common finding in the general population and it has a strong genetic contribution . Our data are in line with a previously published work reporting a rate of migraine equivalents of 70.3% and motion sickness of 40.5% in a sample of over 1000 pediatric patients mostly with migrainous headaches .…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have emphasized how motion sickness is a common finding in the general population and it has a strong genetic contribution. 29,30 Our data are in line with a previously published work reporting a rate of migraine equivalents of 70.3% and motion sickness of 40.5% in a sample of over 1000 pediatric patients mostly with migrainous headaches. 31 Another recent review on migraine precursors reported a rate of 1.9-2.3% for cyclic vomiting, 1.7-4.1% for episodic abdominal pain, and 2-2.6% for episodic vertigo in the total pediatric population.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to VIMS, women have sometimes (but not always) been found to be more susceptible to visual stimulation (Flanagan et al, 2005;Klosterhalfen et al, 2006), and for VR headsets nonfit of interpupillary distance in females may contribute (Stanney et al, 2020). There is some evidence that several preexisting medical conditions that have an impact on quality of life are associated with raised motion sickness susceptibility, including dizziness (Bronstein et al, 2010;Golding and Patel, 2017), proneness to syncope (i.e., feeling of faintness; Bosser et al, 2006), worse sleep quality (Kaplan et al, 2017), and personality factors such as trait anxiety or neuroticism (although often weak effects; Reason and Brand, 1975). Some special groups have reduced or heightened risk: Individuals who have complete bilateral loss of labyrinthine (vestibular apparatus) function are largely immune to motion sickness (Kennedy et al, 1968;Cheung et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Migraine, patients with severe migraine attending migraine clinics. (Adapted from Golding and Patel 2017 58. )…”
mentioning
confidence: 99%